Position-dependent spin–orbit coupling for ultracold atoms. (31st March 2015) - Su, S-W; Gou, S-C; Liu, I-K; Spielman, I B; Santos, L; Acus, A; Mekys, A; Ruseckas, J; Juzeliūnas, G
Abstract: We theoretically explore atomic Bose–Einstein condensates (BECs) subject to position-dependent spin–orbit coupling (SOC). This SOC can be produced by cyclically laser coupling four internal atomic ground (or metastable) states in an environment where the detuning from resonance depends on position. The resulting spin–orbit coupled BEC (SOBEC) phase separates into domains, each of which contain density modulations—stripes—aligned either along the x or y direction. In each domain, the stripe orientation is determined by the sign of the local detuning. When these stripes have mismatched spatial periods along domain boundaries, non-trivial topological spin textures form at the interface, including skyrmions-like spin vortices and anti-vortices. In contrast to vortices present in conventional rotating BECs, these spin-vortices are stable topological defects that are not present in the corresponding homogenous stripe-phase SOBECs.